2014
DOI: 10.1111/iju.12392
|View full text |Cite
|
Sign up to set email alerts
|

Artificial urinary sphincter for post‐prostatectomy incontinence: A review

Abstract: Abstract:The artificial urinary sphincter remains the gold standard for treatment of postprostatectomy urinary incontinence. The AMS 800 (American Medical Systems, Minnetonka, MN, USA) is the most commonly implanted artificial urinary sphincter. Having been on the market for almost 40 years, there is an abundance of literature regarding its use, but no recent review has been published. We reviewed the current literature regarding the indications, surgical principles, outcomes and complications of artificial ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 46 publications
2
71
0
2
Order By: Relevance
“…A literature review noted complication rates and continence outcomes were not affected by previous radiation. 5 Thus it is reasonable to conclude that the increased incidence of radiation in the AUS group, though making it more technically challenging, may not significantly affect our comparison.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A literature review noted complication rates and continence outcomes were not affected by previous radiation. 5 Thus it is reasonable to conclude that the increased incidence of radiation in the AUS group, though making it more technically challenging, may not significantly affect our comparison.…”
Section: Discussionmentioning
confidence: 86%
“…James and McCammon reviewed 9 studies and found an infection rate of 0.5% to 10.6%, comparable to the 4.2% infection rate in this study. 5 The introduction of an antibiotic InhibiZone coating to the AUS was intended to decrease the infection rate. However, a study retrospectively comparing 426 patients evenly treated with and without InhibiZone coated AUS found no difference in infection rates, but a significantly increased cost associated with the coating (about $1300/ device).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ZSI 375 previous series outcomes have shown excellent short-term results, which ranged from 87 to 94.2% (15)(16)(17). Regarding the AMS 800 numerous studies, disparate continence rate are presented from total continence ≤ 90% (4,5,(18)(19)(20) to 73% of patients dry or substantially dry and 88% showing improvement (21). Our social continence rate and success rate of the 12, 24 and 36 months follow-up period meet AMS 800 performances.…”
Section: Discussionmentioning
confidence: 99%